Direito à imunidade tributária das fundações públicas de direito privado - Wagner, Rafael Korff (2023)
The present study aimed to analyze the applicability of tax immunity to public foundations governed by private law, with emphasis on reciprocal tax immunity and immunity to education and social assistance entities, based on the Federal Constitution (CF) of 1988, the constitutional principles and Brazilian jurisprudence. Using a methodology based on bibliographical and documentary research, the analysis encompassed relevant legislation, doctrine and jurisprudence. The investigation highlighted the relevance of Administrative Law and Public Administration within the scope of the State, as well as the importance of understanding the characteristics of the entities that make up the Indirect Public Administration. It was found that the application of reciprocal immunity and immunity to education and social assistance entities and public foundations under private law remains controversial in Brazilian doctrine and jurisprudence. The reciprocal immunity, provided for in article 150, VI, "a", of CF/1988, and immunity to education and social assistance entities constitute essential mechanisms to protect public entities regarding the payment of taxes. However, jurisprudence is still not unanimous regarding the extension of these immunities to such foundations. The decision of the Federal Supreme Court (STF) in the Direct Action of Unconstitutionality (ADI) 4,197, recognizing the constitutionality of the creation of such entities to provide public health services, added elements to the debate. The research identified the need for specific regulation on the extension of immunity to public foundations under private law, as well as a necessary jurisprudential consolidation in determining its applicability. In addition, the importance of strict supervision was emphasized to prevent possible abuses in the use of these entities by the Public Power. Continuing the study and debate on the subject is crucial to improve legal understanding and contribute to the development of solid jurisprudence, ensuring the provision of efficient public services in line with current constitutional principles